A simulink toolbox for software GPS receiver - Wang, Wei (2010)
The objective of final year project is to develop a Simulink toolbox for GPS receiver. It incorporates Simulink and Matlab functions. The toolbox can be used for academic demonstration as well as algorithm investigation. The report covers the introduction, design and implementation of GPS receiver toolbox. It acquires, processes digitized GPS signals, and eventually plots out the geographical location of receiver in latitude-longitude coordinate system. The program consists of four segments: probeData, acquisition, tracking and positioning. As a whole they work closely with each other to process signals, on the other hand each segment is able to run its own provided the inputs are stored in files beforehand. In the end the simulation results of whole program as well as individual segment are displayed and discussed.